Effect of Modeling Techniques on the Simulation: Calculating the Stress Concentration Factors in Square Hollow Section T-Joints as a Case Study - Talabani, Serwan S. M.; Azeez, Ahmad T.; Barros, Silvio D.; Fadhil, Basim M; Omer, Hewa H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
The capability of the simulation software motivates the engineers to analyze the stress in complex welded joints where ordinary mathematical expression may lack. However, unfortunately, the simulations were interpreted mechanically without considering the simulation parameters deeply. For this reason, this research aims to study the effect of simulation parameters on the stress concentration factor of square hollow sections structures using ANSYS workbench. In this context, two main meshing techniques (face split vs. slicing) and various behavior of materials (linear vs. nonlinear) having been considered. The outputs of the investigations revealed the superiority of the materials nonlinearity over linear behavior in terms of results acceptability comparing to their corresponding real-life ones. For instance, the supercritical fluid of nonlinear plastic material estimated to be 14 which was closest to the 12 obtained experimentally by Mashiri et al. In addition to that, face split technique outperformed the slicing in terms of result accuracy and solving time. Solving the face split model elapsed 254 s only which is dramatically less than the minimum time (1605 s) of sliced models. This is because any slicing process will lead to the formation of the contact elements at interfaces and uncomfortable meshing which may in turn adversely effect on the simulation efficiency.